GOLDEN2-like1 is sufficient but not necessary for chloroplast biogenesis in mesophyll cells of C4 grasses - Lambret-Frotte, J; Smith, G; Langdale, J (Wiley, 2023)
Chloroplasts are the site of photosynthesis. In land plants, chloroplast biogenesis is regulated by a family of transcription factors named GOLDEN2-like (GLK). In C4 grasses, it has been hypothesized that genome duplication events led to the sub-functionalization of GLK paralogs (GLK1 and GLK2) to control chloroplast biogenesis in two distinct cell types: mesophyll and bundle sheath cells. Although previous characterization of golden2 (g2) mutants in maize has demonstrated a role for GLK2 paralogs in regulating chloroplast biogenesis in bundle sheath cells, the function of GLK1 has remained elusive. Here we show that, contrary to expectations, GLK1 is not required for chloroplast biogenesis in mesophyll cells of maize. Comparisons between maize and Setaria viridis, which represent two independent C4 origins within the Poales, further show that the role of GLK paralogs in controlling chloroplast biogenesis in mesophyll and bundle sheath cells differs between species. Despite these differences, complementation analysis revealed that GLK1 and GLK2 genes from maize are both sufficient to restore functional chloroplast development in mesophyll and bundle sheath cells of S. viridis mutants. Collectively our results suggest an evolutionary trajectory in C4 grasses whereby both orthologs retained the ability to induce chloroplast biogenesis but GLK2 adopted a more prominent developmental role, particularly in relation to chloroplast activation in bundle sheath cells.